Fat confounds the observed apparent diffusion coefficient in patients with hepatic steatosis - Hansmann, Jan; Hernando, Diego; Reeder, Scott B. (Magnetic resonance in medicine, 2013)
Purpose: Triglyceride signal contained in peaks near the water peak remains unsuppressed by conventional fat suppression techniques used in diffusion-weighted imaging. In this work, we investigated the dependence of the apparent diffusion coefficient (ADC) on liver fat content and whether it is confounded by fat signal. Methods: 43 patients underwent liver diffusion-weighted imaging (b = 0, 500 s/mm2) and single-voxel MR-spectroscopy. Proton density fat-fraction (PDFF; range 0.23-34.5%) was measured from MR-spectroscopy. A theoretical model was developed to account for the effects of fat on observed ADC, and used to correct the ADC. Linear correlation analysis was performed to assess the relationship between PDFF and ADC before and after correction. Results: Linear correlation analysis showed an inverse dependence between observed ADC and PDFF before correction (r2 = 0.132; P = 0.017), and no dependence after correction (r2 = 0.033; P = 0.24). Conclusion: The observed decrease in ADC in patients with fatty liver is, at least in part, artifactual due to residual fat signal near the water peak. Magn Reson Med, 2013. © 2012 Wiley Periodicals, Inc.
Published online: 14 November 2012
Gesehen am 26.07.2018